Between Trees and Maps. Genealogy and Cartography in a Franciscan Painting - Miravalles, Camila (Quiroga. Revista de patrimonio iberoamericano, 2022)
In this article, we intend to examine Mapa de la Grandeza de la Orden de los Menores, an oil painting executed around 1716 in Itatí, a Franciscan mission of Guaraní People and currently located in the Museo del Convento Franciscano of Buenos Aires. We propose to delve into the convergences between the iconography of the family trees of the religious orders and the compositional model offered by the maps produced during the so-called Golden Age of cartography.